Quantitative and Multiplexed Fluorescence Lifetime Imaging of Intercellular Tensile Forces. (10th June 2021) - Keshri, Puspam; Zhao, Bin; Xie, Tianfa; Bagheri, Yousef; Chambers, James; Sun, Yubing; You, Mingxu
Abstract: Mechanical interactions between cells have been shown to play critical roles in regulating cell signaling and communications. However, the precise measurement of intercellular forces is still quite challenging, especially considering the complex environment at cell–cell junctions. In this study, we report a fluorescence lifetime‐based approach to image and quantify intercellular molecular tensions. Using this method, tensile forces among multiple ligand–receptor pairs can be measured simultaneously. We first validated our approach and developed lifetime measurement‐based DNA tension probes to image E‐cadherin‐mediated tension on epithelial cells. These probes were then further applied to quantify the correlations between E‐cadherin and N‐cadherin tensions during an epithelial–mesenchymal transition process. The modular design of these probes can potentially be used to study the mechanical features of various physiological and pathological processes. Abstract : A fluorescence lifetime imaging‐based cell membrane‐anchored DNA hairpin probe is designed to measure tensile forces at cell–cell junctions. The tension among multiple ligand–receptor pairs can be quantified simultaneously during cellular processes such as the epithelial–mesenchymal transition.